Strategi Implementasi Manajemen Pendidikan Berbasis Sekolah - Nona Kumala Sari (Hikmah, 2018)
School-based education management is an implementation of regional autonomy policy. If the autonomy policy requires the region concerned to administer and manage independently, then so does education. In this case the School which becomes the lowest organizational structure is given the authority to manage and manage their own resources. Implementation of MPBS is expected to trigger equity, and accelerate the improvement of the quality of national education. So that each region can compete to improve the quality of the institution. Of course in the implementation of achievement of success depends on the ability of school leaders in planning, implementing, and oversee all resources owned.